Effect of Gamma-irradiation on the Fatty Acid Composition of Salted, Semi-dried Vietnamese Scad and Bombay duck - P.Q., Vinh; V.S., Rao; H.R., Adhikari; P.M., Nair (Fishery Technology, 2025)
Effect of gamma irradiation on the lipid and fatty acid composition of semi-dried Bombay duck (Harpodon nehcreus) and Vietnamese scad (Alepes mate) was studied. In both these dried fishes, c16:0 aand c18:1 were the predominant fatty acids and the fishes contained ignificant quantities of the n-3 polyunsaturated fatty acids (PUFAs}, C20:5 and C22:6. Irradiation at a dose of 3 kGy, did not cause any alterations in the total lipid content and he overall lipid class profile in these fishes. However, in the Vietnamese scad, C18:3, C20:4 and C22:6 were significantly decreased in the irradiated samples. In spite of this decrease the rradiated semi-dried scad retained 82% of the initial amount of n-3 PUFAs.